2017
DOI: 10.1139/cgj-2016-0564
|View full text |Cite
|
Sign up to set email alerts
|

Soil restraints on buried pipelines subjected to reverse-fault displacement

Abstract: The interaction between a buried pipeline and surrounding soil during large ground displacements is typically simulated using numerical nonlinear soil-restraint springs aligned with the longitudinal axis of the pipeline and in the two directions orthogonal to it. There are only very limited experimental data available to characterize the soil springs for simulating pipelines crossing reverse faults where large oblique soil displacements relative to the pipe could occur. Full-scale model testing was undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 20 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…In an overall sense, the graphical shape of the observed lateral force versus displacement relationship is similar to those typically observed in previous lateral soil restraint tests (Wijewickreme et al, 2017;Trautmann and O'Rourke, 1985).…”
Section: Lateral Soil Restraints: Experimental Force-displacement Responsesupporting
confidence: 80%
See 1 more Smart Citation
“…In an overall sense, the graphical shape of the observed lateral force versus displacement relationship is similar to those typically observed in previous lateral soil restraint tests (Wijewickreme et al, 2017;Trautmann and O'Rourke, 1985).…”
Section: Lateral Soil Restraints: Experimental Force-displacement Responsesupporting
confidence: 80%
“…A series of full-scale physical model testing was undertaken by Wijewickreme et al (2017) to evaluate this complex soil-pipe interaction problem by testing the performance of the 400-mm diameter (nominal pipe size, NPS 16) pipe specimens buried in moist sands and crushed limestone trench backfill. The oblique soil restraint values were found to depend significantly on the internal friction angle (φ ) of soil when the pipe movement was closer to the horizontal axis; whereas, the soil restraint was less sensitive to φ when the oblique movement was higher than about 35 • with respect to the horizontal axis.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the innovative work of Vazouras et al (2010), the continuum model is employed by researchers to gain in-depth knowledge of the pipe behavior (e.g. Gawande et al 2019;Rahman and Taniyama 2015;Trifonov 2015;Vazouras et al 2015) and to calibrate numerical models based on experimental results (Fadaee et al 2020;Ni et al 2018;Robert et al 2016;Rofooei et al 2018;Sarvanis et al 2018;Tsatsis et al 2019;Wijewickreme et al 2017). It should be noted that continuum models are typically employed to estimate the pipe-soil interaction in a more accurate manner than the simplified beam-type models because the pipe-soil interface is modeled with contact elements that allow separation and sliding of the soil around the pipe.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The authors performed tests in a soil chamber and found that the uplift resistance of deeply buried pipes in denser soils is lower than the one obtained from ASCE Guidelines. A model was proposed to evaluate the uplift resistance of small diameter pipes in partially saturated sand Wijewickreme et al (2017). executed full-scale experiments modeling pipes under reverse faulting to evaluate the soil mobilization due to the pipe upward movement in the trench with respect to fault dip angle and soil friction angle.…”
mentioning
confidence: 99%
“…Considering the excitation force applied on the lowest point of the pipe along the vertical direction, the pipe will be mainly affected in the vertical direction of the surrounding soil. The outer wall of the pipeline distributed two horizontal and vertical soil springs along the radial direction, which represent the stiffness of the soil, [14][15][16][17] as shown in Figure 2. One end of the spring unit was connected to the pipe and the other end was fixed.…”
Section: Contact Settingmentioning
confidence: 99%